Oxyurichthys omanensis sp. nov., a new Eyebrow Goby (Teleostei: Gobiidae) from Oman - Zarei, Fatah; Jufaili, Saud M. Al; Esmaeili, Hamid Reza (Zootaxa, 2022)
Oxyurichthys omanensis sp. nov. is described as a new gobiid species from a mudflat/estuary habitat in northern Oman. The new species is diagnosed among all currently recognised congeners by the following combination of character states: elongate tentacle on dorsoposterior surface of the eye; nape with well-developed membranous crest; nape scaled to above anterior half of opercle along sides with naked median along membranous crest, scales never reaching to above preopercle; opercle and pectoral base naked; scales ctenoid laterally on trunk posterior to base of second dorsal fin 3rd element; lateral scale rows 51–58, usually 51–56; transverse forward scale rows 23–29, usually 24–28; transverse rearward scale rows 14–16, usually 14–15; upper lip usually constricted at premaxillary symphysis; infraorbital transverse papillae row 2 reaching eye margin dorsally and markedly short of longitudinal row d ventrally; additional short transverse papillae rows between rows 2 and 3i present; dark saddle present over caudal peduncle; snout length 34.9–45.4% HL; second dorsal-fin longest ray 1.1–1.6 head depth; pelvic fin always reaching or passing anal-fin origin. The K2P genetic distances (%) in the mtDNA COI barcode region between O. omanensis and the other Oxyurichthys species were all high (11.2–30.6%) with the K2P nearest neighbor distance of 11.2% to O. cornutus and O. ophthalmonema.